Lower educational level is a predictor of incident type 2 diabetes in European countries: the EPIC-InterAct study - Sacerdote, Carlotta; Kaaks, Rudolf; Teucher, Birgit (International journal of epidemiology, 2012)
Abstract Background: Type 2 diabetes mellitus (T2DM) is one of the most common chronic diseases worldwide. In high-income countries, low socioeconomic status seems to be related to a high incidence of T2DM, but very little is known about the intermediate factors of this relationship. Method: We performed a case-cohort study in eight Western European countries nested in the EPIC study (n = 340, 234, 3.99 million person-years of follow-up). A random sub-cohort of 16,835 individuals and a total of 12,403 incident cases of T2DM were identified. Crude and multivariate-adjusted hazard ratios (HR) were estimated for each country and pooled across countries using meta-analytical methods. Age-, gender- and country-specific relative indices of inequality (RII) were used as the measure of educational level and RII tertiles were analysed. Results: Compared with participants with a high educational level (RII tertile 1), participants with a low educational level (RII tertile 3) had a higher risk of T2DM [HR: 1.77, 95% confidence interval (CI): 1.69-1.85; P-trend < 0.01]. The HRs adjusted for physical activity, smoking status and propensity score according to macronutrient intake were very similar to the crude HR (adjusted HR: 1.67, 95% CI: 1.52-1.83 in men; HR: 1.88, 95% CI: 1.73-2.05 in women). The HRs were attenuated only when they were further adjusted for BMI (BMI-adjusted HR: 1.36, 95% CI: 1.23-1.51 in men; HR: 1.32, 95% CI: 1.20-1.45 in women). CONCLUSION: This study demonstrates the inequalities in the risk of T2DM in Western European countries, with an inverse relationship between educational level and risk of T2DM that is only partially explained by variations in BMI.